2004
DOI: 10.1007/s00034-004-0808-6
|View full text |Cite
|
Sign up to set email alerts
|

A Simplicial Canonical Piecewise Linear Adaptive Filter

Abstract: A new adaptive nonlinear filter realization is presented based on a canonical piecewise linear (CPWL) approach. This filter realization consists of a linear part represented by a finite impulse response filter and a zero-memory nonlinear part implemented as a CPWL map. The resultant structure requires fewer parameters than other realizations found in the literature with comparable modeling capabilities. As a consequence, the proposed nonlinear filter, in addition to its simple description, has low computation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…The parameters β i divide the domain in equal partitions, with β 1 ≤ β 2 ≤ · · · ≤ β σ . From (5) it is clear that the nonlinear gain implicitly includes a saturation behavior. The structure of the SCPWL model considered in this study is shown in Fig.…”
Section: B Simplicial Canonical Piecewise-linear (Scpwl) Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The parameters β i divide the domain in equal partitions, with β 1 ≤ β 2 ≤ · · · ≤ β σ . From (5) it is clear that the nonlinear gain implicitly includes a saturation behavior. The structure of the SCPWL model considered in this study is shown in Fig.…”
Section: B Simplicial Canonical Piecewise-linear (Scpwl) Modelmentioning
confidence: 99%
“…In this paper, we propose a simplicial canonical piecewiselinear (SCPWL) model [4], [5] based DPD to compensate for nonlinear distortion introduced by a HPA in OFDM systems. The simiar study has been reported in [6], in which the same SCPWL function was employed but only the normalized amplitude modulation to amplitude modulation (AM/AM) response was considered.…”
Section: Introductionmentioning
confidence: 99%
“…The conventional SCPWL function in [4] only fits for R 1 domain and allows the representation of any arbitrary continuous nonlinearity between two real-valued variables. Thus, the polar structure becomes the inevitable choice for baseband complex-valued signal modeling, especially in the digital predistortion system.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a piecewise linear function known as the simplicial canonical piecewise linear (SCPWL) function [8] has been proposed for modeling PA and PD characteristics [9], [10]. The order of the SCPWL function in terms of IMD products cannot be directly observed in its transfer function, as can be done for a polynomial model.…”
Section: Introductionmentioning
confidence: 99%